Radical quenching synergistic flame-retardant PET transparent composite material and preparation method thereof

CN122037492BActive Publication Date: 2026-09-04DONGGUAN YUANFENG POLYMER MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610365385.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-03-24
Publication Date
2026-09-04
Estimated Expiration
2046-03-24

AI Technical Summary

Technical Problem

[0007]本发明旨在一种自由基猝灭协效阻燃PET透明复合材料及制备方法,解决现有PET复合材料的透明性、光稳定性和阻燃性能难以同时兼顾的技术问题

Benefits of technology

[0054] 1. The preparation process of this invention is simple and easy to control, with low requirements for production equipment, high production efficiency, and significantly reduces the amount of expensive flame retardants added, thus greatly reducing production costs. The free radical quenching synergistic flame retardant PET transparent composite material prepared by this invention is widely used in fields with high requirements for transparency and fire safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122037492B_ABST
    Figure CN122037492B_ABST
Patent Text Reader

Abstract

The application discloses a kind of free radical quenching synergistic flame-retardant PET transparent composite material and preparation method, first using silane coupling agent graft DOPO and melamine on the surface of layered nanomaterial, and the layered nanomaterial with free radical quenching function is prepared;The PET composite material prepared in the application has high transparency, good light stability and excellent flame-retardant performance, DOPO and alkoxyl hindered amine light stabilizer synergistically play the role of efficient free radical quenching, provide excellent light stabilizing effect at room temperature, inhibit the free radical chain degradation reaction of PET at high temperature, low flame retardant addition amount and the dispersion state of micro-nano size level, so that the PET composite material maintains high transparency.The free radical quenching synergistic flame-retardant PET transparent composite material prepared in the application is widely used in the field with higher requirements for transparency and fire safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to flame-retardant PET materials, and more particularly to a free radical quenching synergistic flame-retardant transparent PET composite material and its preparation method. Background Technology

[0002] Polyethylene terephthalate (PET) is an engineering plastic with excellent overall performance. It not only possesses superior mechanical strength, chemical resistance, and moldability, but also boasts exceptional transparency and gloss, giving it an appearance comparable to glass. Due to its transparency, transparent PET is widely used in the outer protective shells of solar panels, diffusers for lighting equipment, and skylights in buildings.

[0003] However, PET faces two key challenges when used long-term in the aforementioned scenarios. First, its molecular chains are prone to breakage and oxidation under ultraviolet (UV) irradiation, leading to yellowing and brittleness (i.e., UV aging), severely impacting its lifespan and aesthetics. Therefore, UV stabilizers must be added to improve its light stability. Second, as a flammable material, PET requires flame-retardant modification in many applications to meet safety standards.

[0004] Currently, while mainstream halogen-free flame retardants meet environmental protection requirements, their flame retardant efficiency is relatively low. They usually require a large amount of flame retardant (generally ≥25 phr) to achieve the ideal flame retardant rating (such as UL94 V-0).

[0005] High amounts of flame retardants can have serious negative effects: on the one hand, the refractive index of flame retardant particles does not match that of the PET matrix, and when added in large quantities, phase separation can easily occur in the system, resulting in severe light scattering, which significantly reduces the transparency of PET or even makes it opaque; on the other hand, flame retardants can easily have antagonistic effects with light stabilizers, which can impair the UV aging resistance of composite materials.

[0006] Therefore, how to endow PET with high flame retardant properties while maintaining its high transparency and UV aging resistance through technological innovation has become a challenging task with significant practical importance in the field of PET composite materials. Summary of the Invention

[0007] The present invention aims to provide a free radical quenching synergistic flame-retardant transparent PET composite material and its preparation method, thereby solving the technical problem that it is difficult to simultaneously achieve transparency, light stability and flame retardant properties in existing PET composite materials.

[0008] To solve the above-mentioned technical problems, the present invention provides a method for preparing a free radical quenching synergistic flame-retardant PET transparent composite material, comprising the following steps:

[0009] Step S1: Prepare silane-modified layered nanomaterials;

[0010] Step S1.1: First, add the dried layered nanomaterials and solvent A into the reaction vessel. After stirring, the layered nanomaterials are dispersed in solvent A, and the mass concentration is adjusted to 0.5-2.5 wt%.

[0011] Step S1.2, oil bath reaction: Nitrogen gas is introduced into the reaction vessel to heat the temperature of the reaction vessel to 80-120℃, and the oil bath reaction is carried out under nitrogen protection.

[0012] Step S1.3: Prepare the first solution by dissolving the silane coupling agent in solvent B, wherein the mass ratio of the silane coupling agent to the layered nanomaterial is 0.2:1 to 1:1, to obtain the first solution;

[0013] Step S1.4: Reflux reaction. The first solution is slowly added dropwise to the reaction vessel, and after reflux reaction, silane-modified layered nanomaterials are obtained.

[0014] Step S2: Preparation of free radical quenching functional layered nanomaterials:

[0015] Step S2.1: Add solvent E to the reaction vessel to adjust the mass concentration of the silane-modified layered nanomaterials obtained in step 1) to 0.5-2.5 wt%.

[0016] Step S2.2: Nitrogen gas is introduced into the reactor for protection, and then DOPO is added for oil bath reaction. The mass ratio of DOPO to silane-modified layered nanomaterials is 0.05:1~0.15:1. The oil bath reaction temperature is set to 100-150℃ and the oil bath reaction time is 4-12h.

[0017] Step S2.3: Prepare a melamine solution by dissolving melamine in solvent F, with the mass ratio of melamine to silane-modified layered nanomaterials being 0.03:1 to 0.08:1, to obtain a melamine solution with a concentration of 2-10 wt%.

[0018] Step S2.4: Slowly add the melamine solution dropwise into the reaction vessel over 30-120 minutes, adjust the reaction temperature to 80-130℃, and the reaction time to 4-12 hours;

[0019] Step S2.5: After separating and washing the reaction product obtained in step S2.4, free radical quenching functional layered nanomaterials are obtained;

[0020] Step S3: According to the mass fraction, the base material is 100 parts of polyethylene terephthalate granules. Mix 100 phr of polyethylene terephthalate granules (PET), 2.0-6.0 phr of free radical quenching functional layered nanomaterials, 10.0-15.0 phr of phosphorus-based flame retardant, 0.5-2.5 phr of alkoxy-hindered amine light stabilizer, 1.0-6.0 phr of compatibilizer, 0.2-0.5 phr of anti-drip agent, and 0.2-0.8 phr of antioxidant in a high-speed mixer until homogeneous. Then add it to a twin-screw extruder and obtain a free radical quenching synergistic flame retardant PET transparent composite material through twin-screw melt blending and extrusion.

[0021] In a further technical solution, step S1.1 involves mechanically stirring and ultrasonically dispersing the layered nanomaterial and solvent A for 15-120 minutes to uniformly disperse the layered nanomaterial in solvent A.

[0022] In step S1.4, all of the first solution is slowly added dropwise to the reaction vessel within 30-120 minutes, and the silane-modified layered nanomaterial is obtained after reflux reaction for 12-24 hours.

[0023] In step S2.1, after adding solvent E, mechanical stirring and ultrasonic dispersion are performed for 15-120 minutes.

[0024] In step S2.2, the DOPO is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, a halogen-free flame retardant intermediate, with the molecular formula [missing information]. ;

[0025] In step S2.5, the reaction product obtained in step S2.4 is separated by centrifugation and then washed sequentially with solvent C and solvent D to obtain the free radical quenching functional layered nanomaterial.

[0026] In a further technical solution, step S1.1, the drying process involves drying the layered nanomaterial at 80-120°C for 12-24 hours before the reaction.

[0027] In step S1.4, the product obtained from the reflux reaction is washed three times with solvent A to obtain the silane-modified layered nanomaterial.

[0028] A further technical solution is that the twin-screw extruder is sequentially arranged along the extrusion direction as a feeding section, a compression section, a melting section, a mixing section, a homogenization section, an extrusion section, and a die.

[0029] The temperature of the feeding section in Zone 1 is set to 200-230℃.

[0030] The temperature of the compression section in Zone 2 is set to 220-250℃.

[0031] The temperature of the three-zone melting section is set to 230-260℃.

[0032] The temperature of the mixing section in Zone 4 is set at 240-270℃.

[0033] The temperature of the homogenization section in zone five is set at 245-275℃.

[0034] The temperature of the sixth-zone extrusion section is set to 240-270℃.

[0035] The temperature of the die is set to 235-265℃.

[0036] The screw speed of the twin-screw extruder is set to 250-400 r / min.

[0037] In a further technical solution, the layered nanomaterial is at least one of montmorillonite, hydrotalcite, zirconium phosphate, mica, and layered double hydroxides.

[0038] In a further technical solution, solvent A is at least one selected from acetone, methanol, ethanol, isopropanol, dioxane, toluene, xylene, N,N-dimethylformamide, dimethyl sulfoxide, and ethylene glycol.

[0039] Solvent B is at least one of acetone, methanol, ethanol, isopropanol, dioxane, toluene, xylene, N,N-dimethylformamide, dimethyl sulfoxide, and ethylene glycol.

[0040] The solvent C is at least one selected from acetone, methanol, ethanol, isopropanol, dioxane, toluene, xylene, N,N-dimethylformamide, dimethyl sulfoxide, and ethylene glycol.

[0041] The solvent D is at least one of acetone, methanol, ethanol, isopropanol, dioxane, toluene, xylene, N,N-dimethylformamide, dimethyl sulfoxide, and ethylene glycol;

[0042] The solvent E is at least one of acetone, methanol, ethanol, isopropanol, dioxane, toluene, xylene, N,N-dimethylformamide, dimethyl sulfoxide, and ethylene glycol.

[0043] The solvent F is at least one of acetone, methanol, ethanol, isopropanol, dioxane, toluene, xylene, N,N-dimethylformamide, dimethyl sulfoxide, and ethylene glycol.

[0044] In a further technical solution, the silane coupling agent is at least one of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltriethoxysilane, 3-isocyanate-propyltrimethoxysilane, and 3-isocyanate-propyltriethoxysilane.

[0045] The phosphorus-based flame retardant is at least one of diethyl aluminum hypophosphite, aluminum hypophosphite, resorcinol bis(diphenyl phosphate), and bisphenol A bis(diphenyl phosphate);

[0046] The alkoxy-hindered amine light stabilizer is at least one of Tinuvin 622, Chimassorb 119, Cyasorb UV-3529, and Hostavin 3055 NOW;

[0047] The compatibilizer is at least one of ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, maleic anhydride-grafted polyethylene, styrene-maleic anhydride copolymer, and methyl methacrylate-methacrylic acid copolymer;

[0048] The anti-dripping agent is at least one of polytetrafluoroethylene masterbatch and polytetrafluoroethylene powder;

[0049] The antioxidant is a mixture of a primary antioxidant and a secondary antioxidant, with a mass ratio of primary antioxidant to secondary antioxidant of 0.25:1 to 0.5:1. The primary antioxidant is at least one of antioxidant 1010, antioxidant 1076, antioxidant 1330 and antioxidant 2764, and the secondary antioxidant is at least one of antioxidant 168, antioxidant 626, antioxidant S-9228 and antioxidant TPP.

[0050] In a further technical solution, the anti-drip agent is a mixture of polytetrafluoroethylene masterbatch and polytetrafluoroethylene powder, wherein the mass ratio of polytetrafluoroethylene masterbatch to polytetrafluoroethylene powder is 0.25:1 to 2:1.

[0051] In a further technical solution, the silane coupling agent is a mixture of component A and component B, with a mass ratio of component A to component B of 0.25:1 to 2:1. Component A is at least one of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-(2,3-epoxypropoxy)propyltriethoxysilane, and component B is at least one of 3-isocyanate-propyltrimethoxysilane and 3-isocyanate-propyltriethoxysilane.

[0052] A further technical solution is a free radical quenching synergistic flame-retardant PET transparent composite material, which is prepared by the aforementioned method for preparing a free radical quenching synergistic flame-retardant PET transparent composite material.

[0053] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0054] 1. The preparation process of this invention is simple and easy to control, with low requirements for production equipment, high production efficiency, and significantly reduces the amount of expensive flame retardants added, thus greatly reducing production costs. The free radical quenching synergistic flame retardant PET transparent composite material prepared by this invention is widely used in fields with high requirements for transparency and fire safety.

[0055] 2. In the free radical quenching synergistic flame-retardant PET transparent composite material of the present invention, DOPO and alkoxy-hindered amine light stabilizer synergistically exert gas-phase free radical quenching effect on PET, phosphorus-based flame retardant and melamine synergistically exert condensed phase catalytic char formation effect on PET, while layered nanomaterials exert a layer barrier effect and enhance the char layer. The gas-phase and condensed phase flame retardant mechanisms are efficiently coupled, giving the free radical quenching synergistic flame-retardant PET transparent composite material excellent flame retardant properties.

[0056] 3. The free radical quenching synergistic flame-retardant PET transparent composite material provided by the present invention forms a highly efficient light-stabilizing system with DOPO and alkoxy-hindered amine light stabilizer, which effectively quenches active free radicals and endows the PET composite material with excellent UV aging resistance.

[0057] 4. In the free radical quenching synergistic flame retardant PET transparent composite material provided by the present invention, the amount of flame retardant added is low, and it is uniformly dispersed in PET under the synergistic effect of interfacial compatibilization of compatibilizer and high shear field of twin-screw extruder. Therefore, the free radical quenching synergistic flame retardant PET transparent composite material of the present invention maintains high transparency.

[0058] 5. This invention synthesizes free radical quenching functional layered nanomaterials by grafting DOPO and melamine onto the surface of layered nanomaterials using a silane coupling agent. These nanomaterials are then combined with phosphorus-based flame retardants, alkoxy-hindered amine light stabilizers, compatibilizers, anti-dripping agents, and antioxidants, and uniformly dispersed in PET using a twin-screw extruder under controlled processing conditions to prepare a free radical quenching synergistic flame-retardant transparent PET composite material. The free radical quenching synergistic flame-retardant transparent PET composite material prepared by this invention exhibits excellent flame retardant properties and light stability while maintaining high transparency, effectively improving the service life and safety of transparent PET composite materials and significantly expanding their application areas.

[0059] 6. In this invention, various additives are uniformly dispersed in PET under the synergistic effect of the compatibilizer's interfacial compatibilization and the high shear field of the twin-screw extruder. Free radical quenching functional layered nanomaterials, phosphorus-based flame retardants, and alkoxy-hindered amine light stabilizers together form a novel, highly efficient flame-retardant system. When the free radical quenching synergistic flame-retardant PET transparent composite material of this invention is burned, the interleaved layered nanomaterials form a barrier, creating a high-temperature, oxygen-deficient environment inside the free radical quenching synergistic flame-retardant PET transparent composite material. DOPO and alkoxy-hindered amine light stabilizers are synergistically complementary, forming a highly efficient light-stabilizing additive system at room temperature, and quenching the active free radicals generated by the pyrolysis of PET molecular chains at high temperatures, effectively inhibiting the free radical chain degradation reaction of PET. The pyrophosphate generated by the thermal decomposition of the phosphorus-based flame retardant in this invention fully catalyzes the cross-linking and carbonization reaction of the PET decomposition products. The carbonization products bind the layered nanomaterials together, and under the action of NH3 generated by melamine decomposition, they expand to form a dense surface and porous interior structure, exhibiting excellent heat insulation, oxygen barrier, and flame-retardant effects. The flame-retardant system constructed in this invention requires only extremely low addition amounts to enable PET composite materials to meet flame-retardant requirements. Furthermore, the micro-nano-scale dispersion of additives has minimal impact on the transparency of PET, maintaining its high transparency. The PET composite material provided by this invention combines high transparency, good light stability, and excellent flame-retardant properties, effectively overcoming the challenge of balancing these three properties, and is of great significance to the field of transparent composite materials. Attached Figure Description

[0060] Figure 1 a is a SEM image of the layered nano-zirconium phosphate from Example 1.

[0061] Figure 1 b is a SEM image of the free radical quenching functional layered nanomaterial of Example 1. Detailed Implementation

[0062] Example 1

[0063] 1. Preparation of matrix-quenching functional layered nanomaterials

[0064] 1.1 Preparation of silane-modified layered nanomaterials: Before the reaction, layered zirconium phosphate nanoparticles (CAS No.: 13772-29-7) were dried at 100℃ for 16 h. In a reactor, the layered zirconium phosphate nanoparticles were dispersed in toluene at a concentration of 1.0 wt% by mechanical stirring and ultrasonic dispersion for 60 min. Nitrogen protection was maintained, and the oil bath reaction temperature was set at 110℃. γ-(2,3-epoxypropoxy)propyltrimethoxysilane was dissolved in toluene at a concentration of 5 wt%, with a mass ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to layered zirconium phosphate nanoparticles of 0.5:1. The solution was slowly added dropwise to the reactor over 60 min, and the reaction was refluxed for 18 h. The product was washed three times with toluene to obtain silane-modified layered nanomaterials.

[0065] 1.2 Preparation of free radical quenching functional layered nanomaterials: The silane-modified layered nanomaterials obtained in step 1) were dispersed in N,N-dimethylformamide at a concentration of 1.0 wt% by mechanical stirring and ultrasonic dispersion for 60 min. Under nitrogen protection, DOPO was added at a mass ratio of 0.1:1 to the silane-modified layered nanomaterials. The oil bath reaction temperature was set at 110℃, and the reaction was carried out for 8 h. The reaction temperature was adjusted to 100℃, and melamine (at a mass ratio of 0.05:1 to the silane-modified layered nanomaterials) was dissolved in N,N-dimethylformamide at a concentration of 5 wt%, with a mass ratio of 0.05:1. This solution was slowly added dropwise to the reactor over 60 min, and the reaction was carried out for 8 h. The product was separated by centrifugation and washed successively with N,N-dimethylformamide and ethanol to obtain the free radical quenching functional layered nanomaterials.

[0066] Depend on Figure 1 The SEM image in (a) shows that zirconium phosphate has a smooth, layered structure. After grafting DOPO and melamine, the resulting free radical quenching nano-zirconium phosphate still maintains the layered structure, but the surface becomes rough, indicating that DOPO and melamine have been successfully grafted onto the surface of zirconium phosphate.

[0067] 2. Using polyethylene terephthalate (PET) granules as the base material, 100 phr of polyethylene terephthalate granules, 3.0 phr of free radical quenching functional layered nanomaterials, 12.0 phr of diethyl aluminum hypophosphite, 1.5 phr of light stabilizer Tinuvin 622, 4.0 phr of ethylene-acrylic acid copolymer, 0.4 phr of polytetrafluoroethylene masterbatch, and 0.5 phr of antioxidant are mixed evenly in a high-speed mixer. The antioxidant is a mixture of primary antioxidant 1010 and secondary antioxidant in a mass ratio of 0.4:1. The mixture is then added to a twin-screw extruder for melt blending. The parameters for the twin-screw extruder are as follows: Zone 1 feeding section 220℃, Zone 2 compression section 240℃, Zone 3 melting section 250℃, Zone 4 mixing section 260℃, Zone 5 homogenization section 265℃, Zone 6 extrusion section 260℃, die 255℃, and screw speed 350r / min.

[0068] 3. Various standard samples were prepared by injection molding, and flame retardant performance, transmittance and yellowness index were tested before and after artificial ultraviolet aging. The results are shown in Table 1 and Table 2.

[0069] Example 2

[0070] The main steps and process conditions in this embodiment are the same as in Embodiment 1. The difference between this embodiment and Embodiment 1 is that:

[0071] In step 1.1, the drying temperature of the layered nanomaterials is reduced to 80℃, the drying time is extended to 20h, toluene is replaced with ethanol, and the dropping time of the silane coupling agent solution is shortened to 30min.

[0072] In step 1.2, the mechanical stirring and ultrasonic dispersion time is shortened to 15 min, the dispersion concentration of the free radical quenching functional layered nanomaterial is reduced to 0.5 wt%, the melamine solution concentration is increased to 8 wt%, and ethanol is replaced with methanol;

[0073] In step 2, the addition amount of diethylaluminum hypophosphite is increased to 14.0 phr, the light stabilizer Tinuvin 622 is replaced with the light stabilizer Chimassorb 119 (light stabilizer 119), the addition amount of ethylene-acrylic acid copolymer is increased to 5.0 phr, the main antioxidant is replaced from 1010 to 1330, and the parameters of the twin-screw extruder are changed to: feeding section 1 200℃, compression section 2 220℃, melting section 3 230℃, mixing section 4 240℃, homogenization section 5 245℃, extrusion section 6 240℃, die 235℃, and screw speed 250 r / min.

[0074] The results of flame retardant performance testing, transmittance and yellowness index testing before and after artificial UV aging are shown in Tables 1 and 2.

[0075] Example 3

[0076] The main steps and process conditions in this embodiment are the same as in Embodiment 1. The difference between this embodiment and Embodiment 1 is that:

[0077] In step 1.1, the mechanical stirring and ultrasonic dispersion time is shortened to 30 min, zirconium phosphate is replaced with hydrotalcite, and the reaction temperature is increased to 120℃;

[0078] Step 1.2: The mass ratio of DOPO to silane-modified layered nanomaterials is reduced to 0.05:1, the reaction temperature of the melamine grafting reaction is increased to 110℃, the mass ratio of melamine to silane-modified layered nanomaterials is increased to 0.08:1, and the melamine grafting reaction time is extended to 12h.

[0079] In step 2, the amount of free radical quenching functional layered nanomaterial added was increased to 4.0 phr, the amount of light stabilizer Tinuvin 622 added was increased to 2.0 phr, the ethylene-acrylic acid copolymer was replaced with ethylene-methacrylic acid copolymer, the amount of antioxidant added was reduced to 0.2 phr, the auxiliary antioxidant was replaced from 168 with S-9228, and the mass ratio of primary antioxidant to auxiliary antioxidant was increased to 0.5:1.

[0080] The results of flame retardant performance testing, transmittance and yellowness index testing before and after artificial UV aging are shown in Tables 1 and 2.

[0081] Example 4

[0082] The main steps and process conditions in this embodiment are the same as in Embodiment 1. The difference between this embodiment and Embodiment 1 is that:

[0083] In step 1.1, the drying temperature of the layered nanomaterials is increased to 120℃, the drying time is shortened to 12h, toluene is replaced with dioxane, the dispersion concentration of the layered nanomaterials is increased to 1.5wt%, and the mass ratio of silane coupling agent to layered nanomaterials is reduced to 0.2:1.

[0084] In step 1.2, the mechanical stirring and ultrasonic dispersion time is shortened to 30 min, the mass ratio of DOPO to silane-modified layered nanomaterials is increased to 0.12:1, the reaction temperature of the melamine grafting reaction is increased to 130℃, the solvent of melamine is replaced with dimethyl sulfoxide, and the mass ratio of melamine to silane-modified layered nanomaterials is reduced to 0.04:1.

[0085] In step 2, 13.0 phr of diethyl aluminum hypophosphite is replaced with 11.0 phr of aluminum hypophosphite, the addition of ethylene-acrylic acid copolymer is increased to 6.0 phr, 0.4 phr of polytetrafluoroethylene masterbatch is replaced with 0.2 phr of polytetrafluoroethylene powder, and the parameters of the twin-screw extruder are changed to: feeding section 1 230℃, compression section 250℃, melting section 3 260℃, mixing section 4 270℃, homogenization section 5 275℃, extrusion section 6 270℃, die 265℃, and screw speed 400 r / min.

[0086] The results of flame retardant performance testing, transmittance and yellowness index testing before and after artificial UV aging are shown in Tables 1 and 2.

[0087] Example 5

[0088] The main steps and process conditions in this embodiment are the same as in Embodiment 1. The difference between this embodiment and Embodiment 1 is that:

[0089] In step 1.1, the drying time of the layered nanomaterials is extended to 24 h, γ-(2,3-epoxypropoxy)propyltrimethoxysilane is replaced with 3-isocyanate-propyltriethoxysilane, the mass ratio of silane coupling agent to layered nanomaterials is increased to 0.8:1, the dropping time of the silane coupling agent solution is extended to 90 min, and the reaction time is shortened to 12 h.

[0090] In step 1.2, the reaction temperature of the DOPO grafting reaction is reduced to 80℃ and the reaction time is extended to 12h, while the reaction temperature of the melamine grafting reaction is reduced to 80℃ and the melamine grafting reaction time is shortened to 6h.

[0091] In step 2, the light stabilizer Tinuvin 622 is replaced with the light stabilizer Cyasorb UV-3529 (light stabilizer UV3529), the amount of polytetrafluoroethylene masterbatch added is increased to 0.5 phr, the amount of antioxidant added is increased to 0.8 phr, the primary antioxidant is replaced with 1330 instead of 1010, and the secondary antioxidant is replaced with S-9228 instead of 168.

[0092] The results of flame retardant performance testing, transmittance and yellowness index testing before and after artificial UV aging are shown in Tables 1 and 2.

[0093] Example 6

[0094] The main steps and process conditions in this embodiment are the same as in Embodiment 1. The difference between this embodiment and Embodiment 1 is that:

[0095] In step 1.1, the mechanical stirring and ultrasonic dispersion time is extended to 120 min, zirconium phosphate is replaced with montmorillonite, the dispersion concentration of layered nanomaterials is increased to 2.5 wt%, and the reaction temperature is reduced to 80℃;

[0096] In step 1.2, the dispersion concentration of the free radical quenching functional layered nanomaterial was increased to 1.5 wt%, the dropping time of the melamine solution was extended to 90 min, and ethanol was replaced with acetone;

[0097] In step 2, the amount of free radical quenching functional layered nanomaterial added was reduced to 2.0 phr, the amount of diethyl aluminum hypophosphite added was increased to 15.0 phr, the amount of Tinuvin 622 added was increased to 2.5 phr, and the ethylene-acrylic acid copolymer was replaced with maleic anhydride-grafted polyethylene.

[0098] The results of flame retardant performance testing, transmittance and yellowness index testing before and after artificial UV aging are shown in Tables 1 and 2.

[0099] Example 7

[0100] The main steps and process conditions in this embodiment are the same as in Embodiment 1. The difference between this embodiment and Embodiment 1 is that:

[0101] In step 1.1, the dispersion concentration of the layered nanomaterials is increased to 2.0 wt%, γ-(2,3-epoxypropoxy)propyltrimethoxysilane is replaced with γ-(2,3-epoxypropoxy)propyltriethoxysilane, the concentration of the silane coupling agent solution is reduced to 2 wt%, and the dropping time of the silane coupling agent solution is extended to 120 min.

[0102] In step 1.2, N,N-dimethylformamide is replaced with dimethyl sulfoxide, the reaction temperature of the DOPO grafting reaction is increased to 150°C, the concentration of melamine solution is reduced to 2wt%, and the dropping time is extended to 120 min.

[0103] In step 2, diethylaluminum hypophosphite is replaced with resorcinol bis(diphenyl phosphate), 4.0 phr ethylene-acrylic acid copolymer is replaced with 2.0 phr methyl methacrylate-methacrylic acid copolymer, the primary antioxidant is replaced with 2764, and the mass ratio of primary antioxidant to secondary antioxidant is reduced to 0.25:1.

[0104] The results of flame retardant performance testing, transmittance and yellowness index testing before and after artificial UV aging are shown in Tables 1 and 2.

[0105] Example 8

[0106] The main steps and process conditions in this embodiment are the same as in Embodiment 1. The difference between this embodiment and Embodiment 1 is that:

[0107] In step 1.1, the mechanical stirring and ultrasonic dispersion treatment time is extended to 90 min, zirconium phosphate is replaced with mica, the reaction temperature is reduced to 90℃, the concentration of the silane coupling agent solution is increased to 8 wt%, and the reaction time is extended to 20 h.

[0108] In step 1.2, the mechanical stirring and ultrasonic dispersion time was extended to 90 min, the dispersion concentration of the free radical quenching functional layered nanomaterial was increased to 2.0 wt%, the mass ratio of DOPO to silane-modified layered nanomaterial was increased to 0.15:1, the mass ratio of melamine to silane-modified layered nanomaterial was decreased to 0.03:1, and the melamine grafting reaction time was shortened to 4 h.

[0109] In step 2, the amount of free radical quenching functional layered nanomaterial added was increased to 6.0 phr, the amount of diethyl aluminum hypophosphite added was reduced to 10.0 phr, the 1.5 phr light stabilizer Tinuvin 622 was replaced with 0.5 phr light stabilizer Hostavin 3055 NOW, and the parameters of the twin-screw extruder were changed to: feeding section 1 210℃, compression section 2 230℃, melting section 3 240℃, mixing section 4 250℃, homogenization section 5 255℃, extrusion section 6 250℃, die 245℃, and screw speed 300 r / min.

[0110] The results of flame retardant performance testing, transmittance and yellowness index testing before and after artificial UV aging are shown in Tables 1 and 2.

[0111] Example 9

[0112] The main steps and process conditions in this embodiment are the same as in Embodiment 1. The difference between this embodiment and Embodiment 1 is that:

[0113] In step 1.1, the drying time of the layered nanomaterials was extended to 24 h, toluene was replaced with xylene, γ-(2,3-epoxypropoxy)propyltrimethoxysilane was replaced with 3-isocyanate-propyltrimethoxysilane, the mass ratio of silane coupling agent to layered nanomaterials was increased to 1:1, and the concentration of the silane coupling agent solution was increased to 10 wt%.

[0114] In step 1.2, the reaction temperature of the DOPO grafting reaction is reduced to 60℃ and the reaction time is shortened to 4h, while the reaction temperature of the melamine grafting reaction is reduced to 90℃.

[0115] In step 2, diethylaluminum hypophosphite is replaced with bisphenol A bis(diphenyl phosphate), the amount of ethylene-acrylic acid copolymer added is reduced to 1.0 phr, the amount of polytetrafluoroethylene masterbatch added is reduced to 0.3 phr, the amount of antioxidant added is increased to 0.6 phr, and the main antioxidant is replaced by 1076 instead of 1010.

[0116] The results of flame retardant performance testing, transmittance and yellowness index testing before and after artificial UV aging are shown in Tables 1 and 2.

[0117] Example 10

[0118] The main steps and process conditions in this embodiment are the same as in Embodiment 1. The difference between this embodiment and Embodiment 1 is that:

[0119] In step 1.1, the mechanical stirring and ultrasonic dispersion time is shortened to 15 min, zirconium phosphate is replaced with layered double hydroxide, the dispersion concentration of layered nanomaterials is reduced to 0.5 wt%, the reaction temperature is reduced to 100℃, and the reaction time is extended to 24 h;

[0120] In step 1.2, the mechanical stirring and ultrasonic dispersion time is extended to 120 min, the dispersion concentration of the free radical quenching functional layered nanomaterial is increased to 2.5 wt%, the mass ratio of DOPO to silane-modified layered nanomaterial is reduced to 0.07:1, the solvent of melamine is replaced with ethylene glycol, the mass ratio of melamine to silane-modified layered nanomaterial is increased to 0.07:1, the concentration of melamine solution is increased to 10 wt%, and the dropping time of melamine solution is shortened to 30 min.

[0121] In step 2, the amount of free radical quenching functional layered nanomaterial added was increased to 5.0 phr, the amount of light stabilizer Tinuvin 622 added was reduced to 1.0 phr, the ethylene-acrylic acid copolymer was replaced with styrene-maleic anhydride copolymer, the primary antioxidant was replaced with 1076 from 1010, the secondary antioxidant was replaced with 626 from 168, and the mass ratio of the primary antioxidant to the secondary antioxidant was reduced to 0.3:1.

[0122] The results of flame retardant performance testing, transmittance and yellowness index testing before and after artificial UV aging are shown in Tables 1 and 2.

[0123] Comparative Example 1

[0124] To demonstrate that the present invention can impart excellent flame retardant and UV aging resistance properties to PET substrates, pure PET was used as a comparison.

[0125] Various standard samples were prepared from PET granules by injection molding, and flame retardant performance, transmittance and yellowness index were tested before and after artificial ultraviolet aging. The results are shown in Table 1 and Table 2.

[0126] Comparative Example 2

[0127] To demonstrate that the present invention can effectively improve the flame retardant efficiency of traditional flame retardant systems and maintain the high transparency of PET composite materials, traditional flame retardant PET is used as a comparison.

[0128] 100 phr of PET granules, 18.0 phr of aluminum diethyl phosphite, 4.0 phr of ethylene-acrylic acid copolymer, 0.4 phr of polytetrafluoroethylene masterbatch, and 0.5 phr of antioxidant were mixed evenly in a high-speed mixer. The antioxidant was a mixture of primary antioxidant 1010 and secondary antioxidant in a mass ratio of 0.4:1. The mixture was then added to a twin-screw extruder for melt blending. The parameters of the twin-screw extruder were set as follows: feeding zone 1: 220°C; compression zone 2: 240°C; melting zone 3: 250°C; mixing zone 4: 260°C; homogenization zone 5: 265°C; extrusion zone 6: 260°C; die temperature: 255°C; screw speed: 350 rpm.

[0129] Various standard samples were prepared by injection molding, and flame retardant performance, transmittance and yellowness index were tested before and after artificial ultraviolet aging. The results are shown in Table 1 and Table 2.

[0130] Test methods

[0131] 1. Scanning Electron Microscopy (SEM) Testing: A thermal field emission scanning electron microscope (Carl Zeiss, Germany, model Merlin) was used. The sample was fixed to the sample stage with conductive adhesive and sputtered with gold to improve surface conductivity. The morphology of the sample surface was observed under an accelerating voltage of 5 kV.

[0132] 2. Limiting Oxygen Index (LOI) Test: Performed according to ASTM D2863 standard, with a sample size of 120mm × 6.5mm × 3mm.

[0133] 3. Vertical Burning (UL-94) Test: Conducted according to ASTM 635-2003 standard, with sample dimensions of 127mm × 12.7mm × 3.2mm.

[0134] 4. Artificial UV aging: According to ASTM G154 standard, samples with dimensions of 50mm × 50mm × 2.0mm were subjected to 500h of artificial UV aging.

[0135] 5. Transmittance and yellowness index test: According to ASTM D1003 and ASTM E313 standards, the transmittance and yellowness index of the samples before and after UV aging are tested.

[0136] Table 1 is a comparison table of limiting oxygen index and vertical burning test, and Table 2 is a comparison table of artificial ultraviolet aging, transmittance and yellowness index test.

[0137]

[0138]

[0139] Comparative data from Examples 1-10 in Tables 1 and 2 show that free radical quenching functional layered nanomaterials prepared using layered nanomaterials, silane coupling agents, DOPO, and melamine through different processes, when added to PET in different proportions and under different process conditions along with other phosphorus-based flame retardants, alkoxy-hindered amine light stabilizers, compatibilizers, anti-dripping agents, and antioxidants, all produce PET composite materials with high transparency, good light stability, and excellent flame retardant properties.

[0140] As shown in Table 1, the PET composite material provided by this invention exhibits excellent flame retardant properties. Pure PET (Comparative Example 1) is extremely flammable, with a limiting oxygen index (LOI) of only 20.2%, achieving only UL-94 V-2 rating in the vertical burning test. Diethylaluminum hypophosphite, the most commonly used phosphorus-based flame retardant in PET, has relatively low flame retardant efficiency; adding 18.0 phr (Comparative Example 2) only increased the LOI of the PET composite material to 28.6, achieving only UL-94 V-1 rating in the vertical burning test. In contrast, the flame retardant system provided by this invention exhibits very high flame retardant efficiency. For example, in the PET composite material provided in Example 1, the addition amount of diethylaluminum hypophosphite was only 13.0 phr, yet its LOI reached as high as 33.6%, achieving UL-94 V-0 rating in the vertical burning test. This is because, under the synergistic effect of the compatibilizer's interfacial compatibilization and the high shear field of the twin-screw extruder, various additives are uniformly dispersed in the PET. A novel flame-retardant system is composed of free radical quenching layered nanomaterials, phosphorus-based flame retardants, and alkoxy-hindered amine light stabilizers. When PET composites are exposed to heat, the interwoven free radical quenching layered nanomaterials in this system form a barrier, inhibiting the inward transport of external oxygen and hindering the outward diffusion of internal decomposition gases. Therefore, in the high-temperature, oxygen-deficient environment inside the PET composite, DOPO decomposes to generate PO· or HPO· free radicals, effectively quenching the H· and HO· reactive free radicals generated by the PET molecular chain decomposition. Meanwhile, the alkoxy-hindered amine light stabilizer decomposes to generate NOR· free radicals, effectively quenching the ROO· and R· reactive free radicals generated by the PET molecular chain decomposition. Thus, the synergistic complementarity of DOPO and the alkoxy-hindered amine light stabilizer effectively inhibits the free radical chain degradation reaction of PET. Simultaneously, the phosphorus-based flame retardant thermally decomposes at high temperatures to generate pyrophosphoric acid, catalyzing the cross-linking and carbonization reaction of the PET decomposition products. The carbonization products bind the layered nanomaterials together, forming a continuous char layer. At the same time, melamine decomposes to generate non-flammable gases. This causes the char layer to expand, forming a dense surface and porous interior structure, thus exerting excellent heat insulation, oxygen barrier and flame retardant effects.

[0141] As shown in Table 2, the additive system provided by this invention enables PET composite materials to achieve excellent flame retardant properties while maintaining high light transmittance. Traditional flame retardants have low flame retardant efficiency, requiring high addition amounts to meet flame retardant performance requirements, and severely affecting the light transmittance of PET composite materials. For example, adding 18.0 phr of diethylaluminum hypophosphite (Comparative Example 2) reduces the light transmittance of PET from 93% to 75%. In contrast, the high flame retardant efficiency of this invention significantly reduces the amount of traditional phosphorus-based flame retardants required. Furthermore, under the synergistic effect of interfacial compatibilization by the compatibilizer and the high shear field of the twin-screw extruder, various additives achieve micro-nano-scale dispersion in PET, thus significantly weakening the impact of phosphorus-based flame retardants and other additives on PET transparency. For example, in Example 8, its light transmittance is still as high as 90%.

[0142] Table 2 also shows that the PET composite material provided by this invention exhibits excellent light stability. Transparent PET materials undergo UV aging after long-term exposure to light, leading to yellowing and reduced transparency. For example, in Comparative Example 1, after 500 hours of artificial UV aging, the transparency of PET decreased from 93% to 80%, and the yellowness index increased from 1.8 to 17.6. Traditional phosphorus-based flame retardants further accelerate the UV aging of PET. For example, in Comparative Example 2, after 500 hours of artificial UV aging, its transparency decreased sharply from 75% to 48%, and the yellowness index increased from 9.4 to 52.3. In contrast, the PET composite material provided by this invention has excellent UV aging resistance. For example, in Example 7, after 500 hours of artificial UV aging, its transparency only decreased from 87% to 85%, and the yellowness index only increased from 5.8 to 14.0. This is because the combination of DOPO and the alkoxy-hindered amine light stabilizer has excellent free radical quenching effect, effectively capturing active free radicals generated in the PET composite material at room temperature, significantly inhibiting the UV aging of the PET molecular chain.

[0143] This invention first utilizes a silane coupling agent to graft DOPO and melamine onto the surface of layered nanomaterials, preparing layered nanomaterials with free radical quenching function. Subsequently, these nanomaterials are blended with phosphorus-based flame retardants, alkoxy-hindered amine light stabilizers, compatibilizers, anti-dripping agents, antioxidants, etc., and uniformly dispersed in polyethylene terephthalate (PET) using a twin-screw extruder to obtain a free radical quenching synergistic flame-retardant transparent PET composite material. Compared with existing technologies, the free radical quenching synergistic flame-retardant transparent PET composite material prepared by this invention possesses high transparency, good light stability, and excellent flame-retardant properties. DOPO and the alkoxy-hindered amine light stabilizer synergistically exert a highly efficient free radical quenching effect, providing excellent light stability at room temperature and inhibiting the free radical chain degradation reaction of PET at high temperatures. Furthermore, the catalytic char formation barrier effect of the phosphorus-based flame retardant / melamine / layered nanomaterials on PET endows the PET composite material with excellent flame-retardant properties. The low amount of flame retardant added and the micro-nano-scale dispersion state enable PET composite materials to maintain high transparency.

[0144] The technology provided by this invention overcomes the problem of simultaneously achieving transparency, light stability and flame retardancy in PET composite materials. The prepared free radical quenching synergistic flame retardant transparent PET composite material is widely used in fields with high requirements for transparency and fire safety.

Claims

1. A method for preparing a free radical quenching synergistic flame-retardant transparent PET composite material, characterized in that, By weight, 100 phr of polyethylene terephthalate granules, 2.0-6.0 phr of free radical quenching functional layered nanomaterials, 10.0-15.0 phr of phosphorus-based flame retardant, 0.5-2.5 phr of alkoxy-hindered amine light stabilizer, 1.0-6.0 phr of compatibilizer, 0.2-0.5 phr of anti-drip agent, and 0.2-0.8 phr of antioxidant are mixed evenly in a high-speed mixer, and then added to a twin-screw extruder. The mixture is then melt-blended and extruded through a twin-screw extruder to obtain a free radical quenching synergistic flame-retardant transparent PET composite material. The layered nanomaterial is at least one of montmorillonite, zirconium phosphate, mica, layered double hydroxides; The silane-modified layered nanomaterials are prepared through the following steps. Step S1: Prepare silane-modified layered nanomaterials. Step S1.1: First, add the dried layered nanomaterials and solvent A into the reaction vessel. After stirring, the layered nanomaterials are dispersed in solvent A, and the mass concentration is adjusted to 0.5-2.5 wt%. Step S1.2, oil bath reaction: Nitrogen gas is introduced into the reaction vessel to heat the temperature of the reaction vessel to 80-120℃, and the oil bath reaction is carried out under nitrogen protection. Step S1.3: Prepare the first solution by dissolving the silane coupling agent in solvent B, wherein the mass ratio of the silane coupling agent to the layered nanomaterial is 0.2:1 to 1:1, to obtain the first solution; The silane coupling agent is at least one of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltriethoxysilane, 3-isocyanate-propyltrimethoxysilane and 3-isocyanate-propyltriethoxysilane. Step S1.4: Reflux reaction. The first solution is slowly added dropwise to the reaction vessel, and after reflux reaction, silane-modified layered nanomaterials are obtained. The free radical quenching functional layered nanomaterials were prepared through the following steps. Step S2: Prepare free radical quenching functional layered nanomaterials. Step S2.1: Add solvent E to the reaction vessel to adjust the mass concentration of the silane-modified layered nanomaterials obtained in step 1) to 0.5-2.5 wt%. Step S2.2: Nitrogen gas is introduced into the reactor for protection, and then DOPO is added for oil bath reaction. The mass ratio of DOPO to silane-modified layered nanomaterials is 0.05:1~0.15:

1. The oil bath reaction temperature is set to 100-150℃ and the oil bath reaction time is 4-12h. Step S2.3: Prepare a melamine solution by dissolving melamine in solvent F, with the mass ratio of melamine to silane-modified layered nanomaterials being 0.03:1 to 0.08:1, to obtain a melamine solution with a concentration of 2-10 wt%. Step S2.4: Slowly add the melamine solution dropwise into the reaction vessel over 30-120 minutes, adjust the reaction temperature to 80-130℃, and the reaction time to 4-12 hours; Step S2.5: After separating and washing the reaction product obtained in step S2.4, free radical quenching functional layered nanomaterials are obtained.

2. The method for preparing a free radical quenching synergistic flame-retardant PET transparent composite material according to claim 1, characterized in that: In step S1.1, the layered nanomaterial and solvent A are mechanically stirred and ultrasonically dispersed for 15-120 minutes to uniformly disperse the layered nanomaterial in solvent A. In step S1.4, all of the first solution is slowly added dropwise to the reaction vessel within 30-120 minutes, and the silane-modified layered nanomaterial is obtained after reflux reaction for 12-24 hours. In step S2.1, after adding solvent E, mechanical stirring and ultrasonic dispersion are performed for 15-120 minutes. In step S2.2, the DOPO is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. DOPO is a halogen-free flame retardant intermediate with the molecular formula C. 12 H9O2P; In step S2.5, the reaction product obtained in step S2.4 is separated by centrifugation and then washed sequentially with solvent C and solvent D to obtain the free radical quenching functional layered nanomaterial.

3. The method for preparing a free radical quenching synergistic flame-retardant PET transparent composite material according to claim 1, characterized in that, In step S1.1, the drying process involves drying the layered nanomaterials at 80-120°C for 12-24 hours before the reaction. In step S1.4, the product obtained from the reflux reaction is washed three times with solvent A to obtain the silane-modified layered nanomaterial.

4. The method for preparing a free radical quenching synergistic flame-retardant PET transparent composite material according to claim 1, characterized in that, The twin-screw extruder is sequentially configured along the extrusion direction as a feeding section, a compression section, a melting section, a mixing section, a homogenization section, an extrusion section, and a die. The temperature of the feeding section in Zone 1 is set to 200-230℃. The temperature of the compression section in Zone 2 is set to 220-250℃. The temperature of the three-zone melting section is set to 230-260℃. The temperature of the mixing section in Zone 4 is set at 240-270℃. The temperature of the homogenization section in zone five is set at 245-275℃. The temperature of the sixth-zone extrusion section is set to 240-270℃. The temperature of the die is set to 235-265℃. The screw speed of the twin-screw extruder is set to 250-400 r / min.

5. The method for preparing a free radical quenching synergistic flame-retardant PET transparent composite material according to claim 1, characterized in that, Solvent A is at least one of acetone, methanol, ethanol, isopropanol, dioxane, toluene, xylene, N,N-dimethylformamide, dimethyl sulfoxide, and ethylene glycol; Solvent B is at least one of acetone, methanol, ethanol, isopropanol, dioxane, toluene, xylene, N,N-dimethylformamide, dimethyl sulfoxide, and ethylene glycol. The solvent C is at least one selected from acetone, methanol, ethanol, isopropanol, dioxane, toluene, xylene, N,N-dimethylformamide, dimethyl sulfoxide, and ethylene glycol. The solvent D is at least one of acetone, methanol, ethanol, isopropanol, dioxane, toluene, xylene, N,N-dimethylformamide, dimethyl sulfoxide, and ethylene glycol; The solvent E is at least one of acetone, methanol, ethanol, isopropanol, dioxane, toluene, xylene, N,N-dimethylformamide, dimethyl sulfoxide, and ethylene glycol. The solvent F is at least one of acetone, methanol, ethanol, isopropanol, dioxane, toluene, xylene, N,N-dimethylformamide, dimethyl sulfoxide, and ethylene glycol.

6. A method for preparing a free radical quenching synergistic flame-retardant PET transparent composite material according to any one of claims 1 to 5, characterized in that, The phosphorus-based flame retardant is at least one of diethyl aluminum hypophosphite, aluminum hypophosphite, resorcinol bis(diphenyl phosphate), and bisphenol A bis(diphenyl phosphate); The alkoxy-hindered amine light stabilizer is at least one of Tinuvin 622, Chimassorb 119, Cyasorb UV-3529, and Hostavin NOW; The compatibilizer is at least one of ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, maleic anhydride-grafted polyethylene, styrene-maleic anhydride copolymer, and methyl methacrylate-methacrylic acid copolymer; The anti-dripping agent is at least one of polytetrafluoroethylene masterbatch and polytetrafluoroethylene powder; The antioxidant is a mixture of a primary antioxidant and a secondary antioxidant, with a mass ratio of primary antioxidant to secondary antioxidant of 0.25:1 to 0.5:

1. The primary antioxidant is at least one of antioxidant 1010, antioxidant 1076, antioxidant 1330 and antioxidant 2764, and the secondary antioxidant is at least one of antioxidant 168, antioxidant 626, antioxidant S-9228 and antioxidant TPP.

7. The method for preparing the free radical quenching synergistic flame-retardant PET transparent composite material according to claim 6, characterized in that, The anti-drip agent is a mixture of polytetrafluoroethylene masterbatch and polytetrafluoroethylene powder, with a mass ratio of 0.25:1 to 2:

1.

8. The method for preparing the free radical quenching synergistic flame-retardant PET transparent composite material according to claim 6, characterized in that, The silane coupling agent is a mixture of component A and component B, with a mass ratio of component A to component B of 0.25:1 to 2:

1. Component A is at least one of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-(2,3-epoxypropoxy)propyltriethoxysilane, and component B is at least one of 3-isocyanate-propyltrimethoxysilane and 3-isocyanate-propyltriethoxysilane.

9. A free radical quenching synergistic flame-retardant transparent PET composite material, characterized in that, It is prepared by the method for preparing a free radical quenching synergistic flame-retardant PET transparent composite material according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Halogen-free flame-retardant modified PET / PTT / TPEE composite material

    CN104845127A

  • Nano zirconium phosphate with functions of catalyzing char-forming and quenching free radicals as well as preparation method and application thereof

    CN106519736A